n-3 polyunsaturated fatty acids do not alter immune and inflammation measures in endurance athletes - Nieman, D. C.; Henson, D. A.; McAnulty, S. R.; Jin, F.; Maxwell, K. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
The purpose of this study was to test the influence of 2.4 g/d fish oil n-3 polyunsaturated fatty acids (n-3 PUFA) over 6 wk on exercise performance, inflammation, and immune measures in 23 trained cyclists before and after a 3-d period of intense exercise. Participants were randomized to n-3 PUFA (n = 11; 2,000 mg eicosapentaenoic acid [EPA], 400 mg docosahexaenoic acid [DHA]) or placebo (n = 12) groups. They ingested supplements under double-blind methods for 6 wk before and during a 3-d period in which they cycled for 3 hr/d at ~57% Wmax with 10-km time trials inserted during the final 15 min of each 3-hr bout. Blood and saliva samples were collected before and after the 6-wk supplementation period, immediately after the 3-hr exercise bout on the third day, and 14 hr postexercise and analyzed for various immunefunction and inflammation parameters. Supplementation with n-3 PUFA resulted in a significant increase in plasma EPA and DHA but had no effect on 10-km time-trial performance; preexercise outcome measures; exercise-induced increases in plasma cytokines, myeloperoxidase, blood total leukocytes, serum C-reactive protein, and creatine kinase; or the decrease in the salivary IgA:protein ratio. In conclusion, 6 wk supplementation with a large daily dose of n-3 PUFAs increased plasma EPA and DHA but had no effect on exercise performance or in countering measures of inflammation and immunity before or after a 3-d period of 9 hr of heavy exertion.